E-commerce Acceptance in RA - Abgaryan, Davit (Journal of Sociology: Bulletin of Yerevan University, 2017)
E-commerce acceptance by consumers is critical for e-commerce development locally or globally. To predict consumer acceptance of e-commerce, this study aims to investigate the factors affecting the initial and repeat purchase intentions of online consumers. The proposed model integrates perceived price and past transactions with E-commerce Acceptance Model proposed by P. Pavlou in 2003. To our best knowledge, no previous research integrated above-mentioned two factors with any Technolgy Acceptance Model based e-commerce acceptance model. The data provides strong support for the proposed ecommerce acceptance model by validating the hypotheses. The results indicate that both the perceived price and the past transactions have a strong positive effect on the intention to transact online